Effects of low glycemic index diet on insulin resistance among obese adolescent with non-alcoholic fatty liver disease: a randomized controlled trial (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND Obesity is strongly correlated with insulin resistance (IR) and nonalcoholic fatty liver disease (NAFLD). Some studies suggest that dietary intake with low glycemic index (GI) may prevent IR and reduce the incidences of NAFLD. This study was aimed to determine the effects of low GI diet on IR among obese adolescents with NAFLD. METHODS This study was a randomized controlled trial conducted in two Junior High Schools in Semarang, Indonesia. The subjects were 12-14 years obese students with NAFLD, which divided into intervention and control groups according to schools using block random allocation. The intervention group received nutrition education and lunch diet (low energy, low GI, and low fat); meanwhile, the control group only received nutrition education for 12 weeks. The biochemical evaluation included fasting blood glucose (FBG) and insulin levels. IR was assessed using homeostatic model assessment-insulin resistance (HOMA-IR). RESULTS Thirty-two subjects were enrolled in this study, 16 of which were assigned to the intervention group and the other to the control group. After 12 weeks, the energy and carbohydrate intake reduced in the intervention group (p < 0.05), FBG remained unchanged, and HOMA-IR increased (4.9 [3.7]-7.2 [3.5]) compared to the control group (6.4 [4.9]-5.5 [2.8]) (p < 0.05). Meanwhile, within the control group, there were no significant differences in the energy and carbohydrate intake as well as biochemical variables. CONCLUSIONS Low GI modification diet alone may not reduce IR in the obeseadolescents with NAFLD.